Efficacy and prognostic factors of repeated hepatectomy for postoperative intrahepatic recurrence of hepatocellular carcinoma undergoing initial hepatectomy - Cen, Feng; Sun, Xu; Pan, Zhiping; Yan, Qiang (Frontiers in Medicine, 2023)
Background: Highly postoperative recurrence of hepatocellular carcinoma (HCC) caused poor survival. The therapeutic landscape for HCC is exponentially growing and therapeutic innovations are accompanied by the challenge of comparisons of various treatment strategies. This study assessed the outcomes of repeated hepatectomy (RH) for postoperatively intrahepatic recurrence of HCC undergoing initial hepatectomy (IH) and the independent risk factors of the recurrence for recurrent HCC undergoing repeated hepatectomy (RH). Results: Compared RH Group A with IH Group, the results of clinical pathologies displayed such as AFP, Child-Pugh, HBV-DNA, Tumor number, Liver cirrhosis, Tumor differentiation, Surgical approach and TNM stages were significantly different (P<0.05, each) excluding Tumor number and Tumor size (P>0.05, both). There were no significant differences between RH Group B and RFA Group among above features (P>0.05, each). Although operation time associated with RH Group A was prolonged compared with IH Group (4.35±1.25h vs 3.55±0.92h, P<0.001), intraoperative bleeding was no significant difference (400.00±199.25ml vs 359.40±213.37ml, P=0.204). Hospital time associated with RH Group B was prolonged compared with RFA Group (6.5±0.8d vs 5.5±1.1d, P<0.001), however hospitalization cost was not statistically significant (29009±3806CNY, vs 29944±3752CNY, P=0.202). Serum biomarkers postoperatively in the former were prior significantly to the latter including DB/ALB on 5-day (P<0.05, both) and excluding ALT/AST/TB on 5-day (P>0.05, each). Tumor-free survival time associated with RH Group A was lower than IH Group (medians: 12months vs 22months, P<0.001) howbeit those in RH Group B was significantly higher than RFA group (medians: 15months vs 8months, P<0.001). Those with Age≥50y, Child-Pugh A, negative of HBV-DNA presented as independent risk factors positively impacting the postoperative tumor-free survival rate in the first-year of postoperatively intrahepatic recurrent HCC undergoing RH (P<0.001, respectively). Conclusion: Cancer stages associated with recurrent HCC would be inferior to initial that considered potential of harm related to relapse via undergoing RH. RH could offer better outcomes for recurrent HCC undergoing IH. Compared with the pathological nature of lesions, the better target organ of hepar will be key to ameliorating tumor-free survival for the recurrent HCC undergoing RH.